The Effectiveness of Implementing Local Taxpayer Status Confirmation for Investors in the City of Blitar - Subagia, Agus (JURNAL MERCATORIA, 2024)
This article discusses the effectiveness of confirming the status of regional taxpayers in Blitar City based on the Regulation of the Minister of Home Affairs Number 112 of 2016. This research uses Lawrence Meir Friedman's theory of the legal system and Soerjono Soekanto's theory of Law Enforcement. The results of the legal structure analysis show the success of the Regional Finance and Asset Management Agency (BPKAD) and the One-Stop Investment and Integrated Services Office (DPMPTSP) in coordinating and accessing tax applications, which significantly improves service efficiency. The legal substance of Regulation Number 112 of 2016 has proven effective as the basis for the Regulation of the Mayor of Blitar Number 73 of 2019. Legal culture analysis reveals effective public compliance with the taxpayer's status confirmation procedure before receiving services, without any protests. Thus, implementing the regulation in Blitar City can be considered successful, creating effective cooperation between related agencies, ensuring taxpayer understanding and compliance, and improving the quality of public services.